"Hot Topics in Practice" Webinars: Best Practices for Public Health Webinar Development. (September 2022) - Bekemeier, Betty; Rogers, Megan H.; Rose, Barbara A.; Manchanda, Sarah; Andersen, Katherine O.
Abstract : Context: Online education is well researched in some professions; yet, little evidence exists regarding related quality standards for public health practice—particularly with regard to popular webinar offerings. Our objective was to identify and disseminate best practices in public health webinar development for use in development of high-quality, timely webinars for public health practice. Program: We assessed data from the Hot Topics in Practice monthly webinar series that included public health professionals primarily from US Northwest states as regular webinar participants. Implementation: We conducted a secondary analysis, using participant evaluation data from 9 years of online questionnaires. Subsequent recommendations were developed using participants' responses to postwebinar questionnaires. Thematic analysis of qualitative quarterly reports, as well as 12 years of webinar production team knowledge, supplemented development of best practice recommendations that were not recognized through secondary analysis of respondent questionnaires alone. Evaluation: Participant responses tended to be positive when specific practices were followed. These best practices were identified as follows: Address timely topics on current events; Feature only 1 to 2 speakers; Use a limited number of consistently formatted slides; Stay on schedule and make time for audience questions; Minimize technical difficulties; Use effective storytelling to share lessons and key data; Intentionally foster audience engagement (eg, through audience polling, question and answer); Develop clear learning objectives; Provide appropriate resources for continued learning; and Consider audience feedback for continuous improvements. Discussion: Our team identified essential elements for creating high-quality, engaging webinars for public health learning. Best practice recommendations resulting from this study address gaps in quality standards and provide knowledge needed for making effective learning accessible to public health practice and supportive of advancing the field. Findings were synthesized into a practice guide, And We're Live: Creating Engaging Public Health Webinars, to aid public health learning.